Educational Neuroscience and its Contribution to Math Learning - Antonopoulou, Hera; Halkiopoulos, Constantinos; Gkintoni, Evgenia (Technium Education and Humanities, 2023)
In recent decades, an increasing number of educators have focused on neuroscience to investigate how learning experiences shape the brains and cognitive development of young people. This work seeks to capture the functions of the brain and education within this setting. The goal of educational neuroscience is to expand and integrate the existing knowledge about the biological bases of learning from neuroscience in education. Educational neuroscience focuses on enhancing the learning process using brain-related discoveries. The significance of this investigation is in determining whether educational neuroscience may achieve a redefining of knowledge about mathematics education and learning and how this knowledge can be applied in educational practice.